2004
DOI: 10.1002/hep.20475
|View full text |Cite
|
Sign up to set email alerts
|

Low–Grade Steatosis and Major Changes in Portal Flow As New Prognostic Factors in Steroid–Treated Alcoholic Hepatitis

Abstract: The aim of this study was to assess the prevalence and prognostic value of major alterations of portal flow in patients with steroid-treated alcoholic hepatitis. Fifty patients with severe, histologically proven alcoholic hepatitis were enrolled. Clinical data, liver test results, and hepatic Doppler ultrasound findings were collected at inclusion and at month 2. Patients were followed for 1 year or until death. Major changes in portal flow were defined as reversed or alternating flow in the portal trunk and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Although data on the evolution of liver func-tion at 6 months were available for only a small number of such patients, we observed that approximately half of them still had severe liver insufficiency, with a median Child score of 8.5 (range, [6][7][8][9][10][11][12][13][14] and a median MELD score of 21.5 (range, 12-31) (data not shown). This suggests that, among live non-responders with a Lille score Ն 0.45, only half are no longer at risk of liver-induced death.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although data on the evolution of liver func-tion at 6 months were available for only a small number of such patients, we observed that approximately half of them still had severe liver insufficiency, with a median Child score of 8.5 (range, [6][7][8][9][10][11][12][13][14] and a median MELD score of 21.5 (range, 12-31) (data not shown). This suggests that, among live non-responders with a Lille score Ն 0.45, only half are no longer at risk of liver-induced death.…”
Section: Discussionmentioning
confidence: 88%
“…The following clinical and biological variables were recorded at admission, and biological data were prospectively determined during the treatment period (7,14,21, and 28 days): center, age, sex, alcohol intake, presence of encephalopathy, ascites, survival, bilirubin, prothrombin time, albumin, AST, creatinine, white blood cell count, polymorphonuclear count, and DF. All patients were followed for at least 6 months.…”
Section: Clinical and Biological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Among available therapeutic options, and although some clinicians are reluctant to use corticosteroids, compelling data have shown that this treatment improves short-term survival compared to placebo [1,[3][4][5][6][7][8]. However, novel strategies or molecules are required in light of the fact that approximately 40% of patients treated with corticosteroids die within 6 months [9].…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, Duvoux et al [10] reported that major changes in portal flow were frequent in patients with severe alcoholic hepatitis. In their study, all patients had acute-onchronic liver diseases with liver histology showing F4 (liver cirrhosis) in 88% and F3 in 12%.…”
Section: Discussionmentioning
confidence: 91%